Three-dimensional displacement after a medializing calcaneal osteotomy in relation to the osteotomy angle and hindfoot alignment. Issue 1 (January 2020) - Peiffer, M.; Belvedere, C.; Clockaerts, S.; Leenders, T.; Leardini, A.; Audenaert, E.; Victor, J.; Burssens, A.; ,
Highlights: The amount of medial calcaneal displacement correlates with hindfoot valgus correction. More severe hindfoot valgus is related to a larger inferior calcaneal displacement. Inclination of the osteotomy predicts the postoperative calcaneal displacement. Need for patient-specific pre-operative planning and intra-operative control. Abstract: Background: A medializing calcaneal osteotomy is frequently performed to correct adult-acquired flatfoot deformities, but there is lack of data on the associated three-dimensional variables defining the final correction. The aim of this study was to assess the correlation between the pre-operative hindfoot valgus deformity and calcaneal osteotomy angles and the post-operative calcaneal displacement. Methods: Weight-bearing CT scans obtained pre- and post-operatively were retrospectively analyzed for sixteen patients. Corresponding three-dimensional bone models were used to measure valgus deformity pre- and post-operatively, inclination of the osteotomy and displacement of the calcaneus. Linear regression was conducted to assess the relationship between these measurements. Results: On average, the hindfoot valgus changed from 13.1° (±4.6) pre-operatively to 5.7° (±4.3) post-operatively. A mean inferior displacement of 3.2 mm (±1.3) was observed along the osteotomy with a mean inclination of 54.6° (±5.6), 80.5° (±10.7), −13.7° (±15.7) in the axial, sagittal and coronal planes, respectively. A statistically significant positive relationship (p < .05, R 2 = 0.6) was found between the pre-operative valgus, the axial osteotomy inclination, and the inferior displacement. Conclusions: This study shows that the degree of pre-operative hindfoot valgus and the axial osteotomy angle are predictive factors for the amount of post-operative inferior displacement of the calcaneus. These findings demonstrate the added value of a computer-based pre-operative planning in clinical practice. Level of evidence II Prospective comparative study.